2012
DOI: 10.1167/iovs.12-9512
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Retinal Vascular Reactivity in Individuals with Impaired Glucose Tolerance: A Preliminary Study

Abstract: PURPOSE. To investigate the relationship between vascular function parameters measured at the retinal and systemic level and known markers for cardiovascular risk in patients with impaired glucose tolerance (IGT). METHODS.Sixty age-and sex-matched white European adults (30 with IGT and 30 with normal glucose tolerance [NGT]) were recruited for the study. Fasting plasma glucose, lipids, and 24-hour blood pressure (BP) were measured in all subjects. Systemic vascular and endothelial function was assessed by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…In previous studies, we have already documented that individuals with various levels of cardiovascular risk exhibit abnormal retinal and venous responses to flicker-induced provocation (Mroczkowska et al 2012(Mroczkowska et al , 2013Patel et al 2012;Qin et al 2014). In the present study, in a sample with low CVD risk, decreases in the postflicker constrictory phase of retinal veins were apparent in the middle-aged and older individuals only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have already documented that individuals with various levels of cardiovascular risk exhibit abnormal retinal and venous responses to flicker-induced provocation (Mroczkowska et al 2012(Mroczkowska et al , 2013Patel et al 2012;Qin et al 2014). In the present study, in a sample with low CVD risk, decreases in the postflicker constrictory phase of retinal veins were apparent in the middle-aged and older individuals only.…”
Section: Discussionmentioning
confidence: 99%
“…) and impaired glucose tolerance (Patel et al. ). Therefore, it is possible to use the assessment of retinal microvascular function as an early marker for vascular and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that the flicker light-induced vasodilation is reduced in individuals with diabetes [72][73][74][75][76] and those with impaired glucose tolerance [77], and is further impaired with increasing severity of diabetic retinopathy [72,73]. It has been suggested that endothelial dysfunction may underlie this reduced response in diabetes.…”
Section: Assessing Functional Changes Of the Retinal Microvasculaturementioning
confidence: 99%
“…), altered lipid and oxidative stress marker levels (Seshadri et al. ,b) and impaired glucose tolerance (Patel et al …”
Section: Introductionmentioning
confidence: 99%